PENGENDALIAN MATERIAL SISA (WASTE MATERIAL) (STUDI KASUS PEMBANGUNAN GEDUNG KANTOR PERPUSTAKAAN, ARSIP DAN DOKUMENTASI KABUPATEN SIGI) - Asnudin, Andi; Labombang, Mastura; Fahri, Muzani (JOURNAL TEKNIK SIPIL DAN INFRASTRUKTUR, 2017)
In the process of building construction residual materials usually formed that can be disadvantageous for the work parties.There are several ways to reduce the occurrence of waste material. The purpose of this research is to know how to control the waste material in case study of library office, archive and documentation buildings of Sigi Regency. The data were obtained by distributing questionnaires to the job implementers as well as taking documentation in the field. Data processing were using likert scale method, descriptive analysis, photograph analysis and SPSS software to determine the reliability of a data and correlation using Spearman's Rho method. The results of  this research indicate the control of residual materials carried out by taking into account: (a) the security of material  storage, (b) the storage of materials according to  the type and nature of the material, (c) plotting and calculating material use, (d) the worker's occupational control, (e) the presence of an officer inspecting and recording the material accepted and material that have been used, (f) casting and plastering in accordance with predetermined requirements, (g) the officer recognizing the material type and knowing the material allocation issue, (h) Packaging and control on  transporting materials, (i) storage location can facilitate the distribution of materials to job sites.